BIMBINGAN DAN PENYULUHAN TENTANG PENTINGNYA KUALITAS PELAYANAN DAN PENCATATAN ORDER PESANAN JASA PADA BENGKEL SUDIMORO DIESEL DI MALANG - Joko Samboro; Heru Utomo; Maskur Maskur (Publisher UPT P2M Politeknik Negeri Malang, 2020)
The purpose of this Community Service Program is to find problems faced by partner companies and at the same time provide the right solutions in order to achieve increased sales and knowledge and skills of entrepreneurs in the field of operations, especially in the field of marketing management, as well as creating job opportunities in community economic activity in the form of increased income. Public. The partner of this program is the DIESEL WORKSHOP entrepreneur, Mr. SugiyonoThe problems faced by partners are: 1. Not knowing the importance of good service quality. 2. Do not understand the importance of recording service purchase orders.The solutions offered are: 1. Guidance and training on good service quality. 2.Simulation of the importance of recording service purchase orders can improve the marketing of services, so that the marketing reach will be wider and sales can increase.The method used is: observation, to observe the activities carried out by entrepreneurs in making and marketing services, then interviews, explored to find problems and solutions to be offered and simulations, to find the most suitable alternatives in order to market goods more effectively.Description of technology to be applied.:1. In the form of a Lecture: Participants gathered in a certain room are given a lecture on program materials in the form of marketing management and service quality.2. Guidance and Training: In the form of guidance and training on the implementation of Service Quality and recording service purchase orders and discussing experiences and constraints in the field.3. Practice simulation: In the form of a demonstration of how to carry out Service Quality and recording service purchase orders.The resulting output is in the form of: 1). Scientific Publications in ISSN Journals. 2). Increasing competitiveness. 4). Application of appropriate science and technology / technology